Middle Power Dreaming : Mexico between Aspirations and Reality - Ivanovic, Marija; Gotz Betancourt, Shirley; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This thesis examines the case of Mexico as middle power. More precisely, it tries to see what were the limitations and possibilities that Mexico faced in the period 2000-2012, while trying to engage more in the international system and rise its international profile. The PAN governments that were in power at that time devoted much of their energy trying to better international position of Mexico, and implicitly the thesis will answer the question of how successful were their strategies.
Vedoucí práce: Shirley Gotz Betancourt
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses